2017
DOI: 10.1073/pnas.1701386114
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the ABCs of self-assembly via low-χ block polymer design

Abstract: Block polymer self-assembly typically translates molecular chain connectivity into mesoscale structure by exploiting incompatible blocks with large interaction parameters (χ ij ). In this article, we demonstrate that the converse approach, encoding low-χ interactions in ABC bottlebrush triblock terpolymers (χ AC ≲ 0), promotes organization into a unique mixed-domain lamellar morphology, which we designate LAM P . Transmission electron microscopy indicates that LAM P exhibits ACBC domain connectivity, in contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 70 publications
6
51
0
1
Order By: Relevance
“…For a poly(norbornene)‐based backbone, where L 0 is the length of a single repeat unit ( L 0 = 0.62 nm), l p is estimated to be ~5 repeat units (5 L 0 = 3.1 nm) according to self‐consistent field theory (SCFT) calculations . We determine that the PS side chains size increases from 〈 R sc 〉 = 3.5 nm in Group I to 〈 R sc 〉 = 4.5 nm in Group II, which is on the order of the backbone l p . However, the actual l p of the backbone should increase accordingly with an increase in the PS side chain length, as reflected by the increase in scaling from α = 0.71 to 0.81.…”
Section: Resultsmentioning
confidence: 91%
“…For a poly(norbornene)‐based backbone, where L 0 is the length of a single repeat unit ( L 0 = 0.62 nm), l p is estimated to be ~5 repeat units (5 L 0 = 3.1 nm) according to self‐consistent field theory (SCFT) calculations . We determine that the PS side chains size increases from 〈 R sc 〉 = 3.5 nm in Group I to 〈 R sc 〉 = 4.5 nm in Group II, which is on the order of the backbone l p . However, the actual l p of the backbone should increase accordingly with an increase in the PS side chain length, as reflected by the increase in scaling from α = 0.71 to 0.81.…”
Section: Resultsmentioning
confidence: 91%
“…These effects remain poorly understood. Moreover, the unusual carbon–fluorine bond polarizability provides orthogonal solubility characteristics that can be exploited in block polymer self‐assembly to generate multi‐component micelles and tune interaction parameters . Full exploration of these effects necessitates a wide range of monomer sequences and chemistries.…”
Section: Methodsmentioning
confidence: 99%
“…ABC triblock brushes composed of PLA, poly(methyl methacrylate) (PMMA) and PS—with similar block and side‐chain lengths—revealed similar behaviour to a diblock copolymer with fully segregated PLA and mixed PS/PMMA phases, despite the general immiscibility of PS and PMMA and the miscibility of PLA and PMMA . Similarly Grubbs and co‐workers studied ABC triblock brushes composed of polymers with low interaction ( χ ) parameters . In contrast to linear analogues that typically form two‐ or three‐domain lamellar morphologies, their study revealed the self‐assembly of brushes into lamellar domains with a unique block domain connectivity.…”
Section: Applications Of Compartmentalised Molecular Polymer Brushesmentioning
confidence: 99%